Respostas fisiológicas em cana-de-açúcar submetida à aplicação de piraclostrobina - Lopes, Amanda Moreira (2016)
With the increased search for renewable energy sources, C4 plants have gained prominence as primary sources, among which is the sugarcane (Saccharum spp.). This species is of great economic importance given its wide application in the industrial sector, and especially in the production of ethanol. Considering the increasing interest for ethanol, the investment in new generation technology to increment production have been of great relevance. Therefore, the development of new technologies with the objective of increasing productivity is of paramount importance, given that the energy is cheap, clean and renewable. Many studies have evaluated the possible advantages of different fungicides, among which is the pyraclostrombin, from the strobilurin group. Studies report that, after the application of strobilurin, plants presented physiological changes, such as greener leaves, with more chlorophyll, greater development, increase in liquid photosynthesis, due to the reduction in respiration,; increase of nitrogen assimilation by means of an increase in the activity of enzyme nitrate reductase, causing better hormonal balance, increasing the levels of indolacetic acid (IAA) and abscisic acid (ABA), also decreasing the production of ethanol. We aimed at evaluating the physiological responses of three sugarcane cultivars submitted to the application of the pyraclostrombin-based fungicide. The experiment was divided into two treatments. One was the control, without the application of the fungicide, and the other, applied, with the application of pyraclostrombin fungicide in the dose of 1.0 L ha -1 . Gas exchange, biometric, quantification of photosynthetic pigments, antioxidant enzyme activities and productivity analyses were performed at the following times: 0, 1, 2, 4, 5, 15, 25, 35 and 65 days after application of the fungicide. The plants treated with fungicide presented increase in photosynthetic rate, the activity of the antioxidant enzymes increased, and presented a higher content of green mass and TCH. Based on the results obtained, we conclude that the application of pyraclostrombin promotes an increment of the photosynthetic rate of all three sugarcane cultivars, causing higher biomass accumulation. The plants treated with the fungicide presented greater growth than the plants without the application.